The Effect of the Changing Size and Composition of Government Purchases on Potential Output - von Furstenberg, George M. (The Review of Economics and Statistics, 1980)
and not from the explicit examination of substitutability between private and public provision of goods and services. If private and government investment expenditures are perfect substitutes (the limiting case) then increases in government investment goods purchases financed by additional debt creation reduces potential output because private net-of-deficit savings decline by more than the increase in government investment at the initial level of output. Since government debt is viewed as an addition to wealth there is a decline in the relative desire to accumulate capital goods, whether private or public. Thus, the observation that there may be a potential decrease in steady state output is not due to perfect (or any other degree of) substitutability between private and public expenditures but rather is due to a less than perfect symmetry to the wealth effects associated with tax and deficit financing. The introduction of less-thanperfect' expenditure substitutability mitigates against this revenue composition effect, as a one dollar increase in government investment goods would initially cause a less than one dollar decrease in private investment demand. In like fashion, von Furstenberg's assertion that the marginal propensity to save must be unity if fiscal actions are not to affect steady state output (p. 77) is correct only within the context of his particular private savings function. If future tax liabilities are perfectly discounted then the marginal propensity to save will be unity out of the obtained by the private sector from changes in the form of financing government expenditures. Thus, alluding to an observed savings rate of 8% in the United States does not constitute any substantive evidence about possible impacts on potential output of changes in government expenditures, as that average savings rate cannot be applied to marginal changes in disposable income when future tax liabilities are fully, or even partially, discounted.